O Festival Raízes do Atlântico na ilha da Madeira: autonomia regional, pós-folclorismo e desenvolvimento - Branco, J. F. (2021)
The “Atlantic Roots Festival” has been celebrated yearly since 1999 in Funchal, Madeira. It promotes regional music revival, and has fomented a movement dedicated to the reinterpretation of local tradition within the field of ‘world music’. It has updated regional identity, placing the latter in consonance with cultural dynamics of globalization. An assessment of this event’s contribution to local development indicates various positive elements: civic participation (revealing a new regional identity, with political dimensions), sustainability (curricular revision of artistic performances, along with the cultivation of new musical abilities), and the enlivening of civil society (organization of leisure time activities, diversification of cultural consumption). However, results obtained in the economic sphere have until now been of residual significance.